Features of Style of A.P. Chechov (on a Material of Stories «Long Tongue» and «The Lady with the Doggie») - M B Loskutnikova (RUDN Journal of Studies in Literature and Journalism, 2009)
In the article the style organization of a A.P. Chekhov's stories with one plot base - «Long tongue» (1886) and «The Lady with the doggie» (1899) - is compared each other. Author has revealed the generality and the distinctions connected with deepening of problematics, reconsideration of characters, plot transformation, modality change, genre integration, wide use of means of stylistics.